Term of Office of Constitutional Judges and Its Implications for the Independence of Judicial Power - Dewi Andriani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper analyzes the implications of the term of office of constitutional judges in relation to the principle of independence of judicial power. Constitutional justices have a five-year term of office and can only be re-elected for one further term. This provision has been tried to be corrected through a request for judicial review of the Constitutional Court (MK) Law, but there is no Constitutional Court decision stating that the term of office of constitutional judges is contrary to the 1945 Constitution of the Republic of Indonesia. Determining the term of office of constitutional judges has implications for the independence of judicial power. The existence of a second period or renewable term will open up opportunities for political influence in the appointment of constitutional judges for the second period, thereby reducing the independence of judicial power. The elimination of the second period as approved by the legislators has positive implications for the independence of judicial power, but needs to be accompanied by improvements to the selection and supervision mechanism for constitutional judges. The Third Amendment to the Constitutional Court Law also regulates the selection process, but only states the principles and leaves further regulations to each state institution.